1993
DOI: 10.1093/clinchem/39.6.972
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific immunoenzymometric assay of troponin I in the early phase of acute myocardial infarction

Abstract: The screening by immunoenzymometric assay (IEMA) of 784 monoclonal antibody (MAb) combinations resulted in the selection of an optimal pair of MAbs for measuring human cardiac troponin I (TnI). Using a one-step IEMA described here, we were able to detect TnI within the range of 0.2-20 micrograms/L in 30 min at room temperature. No cross-reactivity was observed with the skeletal isoforms of troponin up to a concentration of 500 micrograms/L. This assay was used to measure cardiac TnI in the plasma of 43 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(56 citation statements)
references
References 0 publications
1
51
0
4
Order By: Relevance
“…Asphyxiated neonates have higher cardiac troponin I (cTnI) concentrations than controls (4). In adults, cTnI appears in serum within a few hours of myocardial injury and peaks at 12-18 h (5).…”
Section: Introductionmentioning
confidence: 99%
“…Asphyxiated neonates have higher cardiac troponin I (cTnI) concentrations than controls (4). In adults, cTnI appears in serum within a few hours of myocardial injury and peaks at 12-18 h (5).…”
Section: Introductionmentioning
confidence: 99%
“…Post-operative ischaemia seems to correlate with adverse outcome, and prolonged subendocardial ischaemia rather than acute coronary artery occlusion precedes cardiac complications [1,6]. Cardiac troponins (TNs) -troponin T (TNT) and troponin I (TNI) -have been established as a sensitive marker for detection of major and minor myocardial cell injury, avoiding the high incidence of false-positive results by the use of creatine kinase (CK)-MB [7][8][9][10][11][12]. Metzler et al [13] found that in cardiac risk patients undergoing non-cardiac surgery high postoperative levels of TNT and TNI were correlated with post-operative cardiac complications, whereas patients with no or only slightly increased concentrations of both troponins had a good outcome.…”
Section: Introductionmentioning
confidence: 99%
“…14 Elevated cardiac troponin I is known to be a marker of myocyte injury and is therefore a valuable tool for the diagnosis of myocardial infarction. 7,13,15,16 Elevated cardiac troponin I concentrations have also been observed in other clinical conditions such as reperfusion therapy monitoring, 17 myocarditis, and in patients with cardiac contusions, 18,19 thus confirming its cardiospecificity.…”
Section: Discussionmentioning
confidence: 78%